2022
DOI: 10.29303/jppipa.v8i1.1186
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Applying Blended Learning Strategies Flipped Classroom Model on Students’ Critical Thinking Skills

Abstract: Critical thinking skills are competencies that are expected to be possessed by every student in 21st century learning. One of the efforts that can be made to improve students' critical thinking skills is to apply the flipped classroom learning model. This study aims to determine the effect of students' critical thinking skills through the application of the blended learning model of the flipped classroom. The research approach used is quantitative with a quasi-experimental type of research, the research design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…The results are in line with those of the studies that affirm that the FC increases academic performance and improves the understanding of subject content compared to the traditional teaching [6,[88][89][90]. In this sense, it is shown that the FC adapts to learning needs and favours the personalisation of teaching [91][92][93]. It also favours autonomous learning, facilitating the acquisition of strategies for learning to learn [94,95].…”
Section: Discussionsupporting
confidence: 89%
“…The results are in line with those of the studies that affirm that the FC increases academic performance and improves the understanding of subject content compared to the traditional teaching [6,[88][89][90]. In this sense, it is shown that the FC adapts to learning needs and favours the personalisation of teaching [91][92][93]. It also favours autonomous learning, facilitating the acquisition of strategies for learning to learn [94,95].…”
Section: Discussionsupporting
confidence: 89%
“…The dissemination stage is carried out by media socialization made to students and lecturers in the physics education study program. IoT (Internet of Think)-based physics practicum media If the user's response is good, then large quantities of production and marketing will be carried out so that the IoT (Internet of Think)-based physics learning media is used by a wider target (Zulhamdi et al, 2022).…”
Section: Development Of Iot (Internet Of Thinks) Based Physics Learni...mentioning
confidence: 99%
“…Students who take part in online learning have an increasingly high interest in learning, and there are also students who, since online learning is carried out, have less interest in learning (Rulandari, 2020). Online learning links educators and students with an internet network that can be accessed anytime and anywhere (Zulhamdi et al, 2022). Online Learning aims to provide quality learning services in a massive and open network (online) to reach more and wider audiences.…”
Section: Introductionmentioning
confidence: 99%